Korean classifier-less number constructions - Ahn, Dorothy (ZAS Papers in Linguistics, 2018)
Korean is a generalized classifier language where classifiers are required for numerals to combine with nominals. This paper presents a number construction where the classifier is absent and the numeral appears prenominally. This construction, which I call the classifier-less number construction (Cl-less NC), results in a definite or a partitive reading where the referent must be familiar: ‘the two women’ or ‘two of the women’. In order to account for this, I argue that Korean postnominal number constructions are ambiguous between a plain number construction and a partitive construction. After motivating and proposing an analysis for the partitive structure, I argue that Cl-less NC is derived from the partitive construction, explaining its distributional restriction and the interpretation. Keywords: number construction, classifiers, partitives, Korean.